Orthodontic retreatment of Class II, Division 1 malocclusion with microdontia using an interdisciplinary approach: A case report - Ryza Yasha; Sarah Fitria Romadhoni; Pinandi Sri Pudyani; Ananto Ali Alhasyimi; Francisco José Vázquez-Santos; Hasna Syifa Yuniva; Diatri Nari Ratih (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Orthodontic treatment failure and unstable treatment results can lead to orthodontic retreatment. Excessive overjet, convexity, and upper and lower lip protrusion are common in Class II malocclusion. When combined with microdontia (smaller-than-average teeth), it presents unique challenges. Purpose: To describe retreatment of Class II, Division 1 malocclusion with microdontia using orthodontic and conservative approaches. Case: A 25-year-old female patient with a skeletal Class II relationship with bimaxillary retrognathism and protrusion of the lower incisors. An intraoral examination showed a Class II molar relationship on the right side, a deep overbite (5.47 mm), a large overjet (5.33 mm), multiple diastemas, and microdontia in tooth 22. Teeth #14, #24, #34, and 44 were extracted during a previous orthodontic treatment. Case management: Orthodontic retreatment was initiated with bracket placement using the edgewise technique. A multiloop archwire was installed to achieve leveling and alignment with a 0.14-inch stainless steel round archwire. Treatment involved bite opening with L loops, mesialization of teeth #11, #21, #12, and #22, retraction of the anterior segment, finishing, and root paralleling. After 22 months of orthodontic treatment, the brackets were debonded, and the patient received direct composite veneer treatment to reshape teeth #12 and #22. Post-retreatment facial evaluation showed a significant improvement in overall facial harmony. Intraoral examination showed Class I molar and canine relationships, good interdigitation, and adequate overbite (2.9 mm) and overjet (3.2 mm). Conclusion: Orthodontic retreatment of a Class II, Division 1 malocclusion with microdontia, when combined with conservative approaches, can significantly improve the patient’s facial profile and stomatognathic function.